2017
DOI: 10.1515/jpm-2016-0284
|View full text |Cite
|
Sign up to set email alerts
|

Impact factors on cervical dilation rates in the first stage of labor

Abstract: Cervical dilation is a hyperbolic increasing process, with faster dilation rates in multiparous compared to nulliparous women and a reversal point of labor around 6-7 cm, respectively. Besides, cervical dilation is highly individual and affected by several impact factors. The diagnosis of labor arrest or prolonged labor should therefore be based on such rates and on the individual evaluation of every woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…few known causal factors influencing first stage duration are maternal age, increasing BMI, posterior fetal position and higher fetal weight [34][35][36][37][38][39][40]. Compared to the African and American cohorts, the Swedish cohort was older, had lower BMI, lower gestational age at birth, and fetal weight was higher.…”
Section: Plos Onementioning
confidence: 99%
“…few known causal factors influencing first stage duration are maternal age, increasing BMI, posterior fetal position and higher fetal weight [34][35][36][37][38][39][40]. Compared to the African and American cohorts, the Swedish cohort was older, had lower BMI, lower gestational age at birth, and fetal weight was higher.…”
Section: Plos Onementioning
confidence: 99%
“…Multiparity was a protective factor of infectious diseases may be because of the shorter time of the duration of labor. It is known that the cervical dilation rates and foetal descent process of multiparous women is faster than that of nulliparous women [ 31 , 32 ], and we concluded that the shorter labor process may be the reason of lower risk of infection.…”
Section: Discussionmentioning
confidence: 72%
“…Duration of is shorter in multiparous compared to nulliparous women, with a range for nulliparous (0.29-1.57 cm/h), and multiparous (0.32-4.47 cm/h) women [4][5][6]. However, comparability between studies is compromised as the de nition of the onset of the active rst stage of labour differs.…”
Section: Duration Of Labourmentioning
confidence: 99%
“…Additionally, Friedman postulated a linear progression curve of 1 cm/h and de ned the beginning of active phase at 3-4 cm [1]. Since, multiple studies have challenged the Friedman curve and found that progression of labour can be slower and non-linear with a range for nulliparous (0.29-1.57 cm/h), and multiparous (0.32-4.47 cm/h) women [4][5][6]. This wide variability of labour progression is most likely explained by an interindividual variation as well as other potential factors, such as the neonatal birthweight or head circumference.…”
Section: Introductionmentioning
confidence: 99%